On the trigonal structure of the ζ-hydride in zirconium: A microstructural characterization approach by electron diffraction and energy-loss spectroscopy. (1st April 2023) - Badr, N.N.; Long, F.; Lou, Y.; Topping, M.; Béland, L.K.; Yao, Z.; Daymond, M.R.
Abstract: The zirconium (Zr) ζ-hydride phase was first proposed in 2008. While electron diffraction experiments characterized a trigonal crystal structure for this phase, formation-energy calculations have predicted that trigonal is not a stable structure for that. In this work, we attempt to tackle this discrepancy between experimental and computational studies. For this purpose, nano-beam electron diffraction (NBED) and electron energy-loss spectroscopy (EELS) were utilized to characterize the crystal structure of nano-hydrides in annealed Zircaloy-2. Diffraction patterns (DPs) collected from multiple axes of precipitates (and identical to those reported for the ζ-hydride in previous works) are shown to be composed of typical α-Zr and δ-hydride reflections along with additional reflections that did not belong to either phase. It is shown that precipitates were δ-hydride and extra reflections did not originate from a trigonal structure. Instead, it is proposed that they originated from either δ-hydride and a thin surface (probably Zr-oxide) phase or double-diffraction scattering between the α-Zr and δ-hydride. Previous works reported a plasmon energy (PE) value of 17.4 ± 0.1 eV for the ζ-phase. PE maps in this work confirmed the δ-nature of the examined nano-hydrides and revealed that the measured 17.4 eV PE value belonged to interfacial ribbons as a normal interface effect, instead of a ζ-phase. Hence, as predicted by computations, it is concluded that the trigonal structure appears to not be the appropriate crystal structure for nano-hydrides and reported observations of the ζ-hydride in the past could, in fact, have been δ-phase that was misidentified. Graphical abstract: Image, graphical abstract